A Case of Eosinophilic Granulomatosis with Polyangiitis Presenting with Mononeuritis Multiplex - Alam, Md. A.; Hossain, Md. Ismail; khan, Abed Hussain; Arafat, Shohael Mahmud (Current Rheumatology Reviews, 2022)
Background: Eosinophilic granulomatosis with polyangiitis (EGPA), also known as Churg Strauss syndrome, is an uncommon vasculitis associated with antineutrophil cytoplasmic antibody (ANCA). The hallmarks of the disease are asthma, eosinophilia, and systemic vasculitis with varying degrees of neurological, cutaneous, cardiac, gastrointestinal, and renal involvement. Diagnosis is often difficult since the symptoms are diverse, and a number of differentials need to be excluded. Case Presentation: In this report, we describe a 60-year-old patient who presented with mononeuritis multiplex and a painful skin rash. A history of late-onset asthma, which was poorly controlled, led us to suspect EGPA. Laboratory data showed leukocytosis, eosinophilia (>10%), elevated ESR, CRP, and IgE, normal chest Xray, positive rheumatoid factor (RA), perinuclear anti-neutrophil cytoplasmic antibody (p-ANCA), and evidence of extravascular eosinophils in histopathology report of skin biopsy. She was treated with methylprednisolone and cyclophosphamide pulse therapy with a satisfactory response. Conclusion: Diagnosis of EGPA requires a combination of clinical and histopathological findings to meet the diagnostic criteria. A history of poorly controlled or late-onset asthma may guide us to the diagnosis that is frequently overlooked. Due to the wide heterogeneity of EGPA patients' phenotypes, sharp, professional judgment is needed for early disease detection and treatment in order to avoid irreversible changes and poor outcomes.
Keywords: Eosinophilic granulomatosis with polyangiitis